(untitled) (Physical Education, Health and Social Sciences, 2025)
Teaching English as a foreign language presents considerable challenges in both rural and urban contexts. Instructors are required to pay close attention to the development of students’ core language skills, namely reading, writing, listening, and speaking. Beyond these fundamental areas, teachers are also expected to integrate modern technology into their teaching practices and foster in students a positive learning environment characterized by enthusiasm, motivation, and a constructive attitude toward mastering English. However, the specific challenges encountered often vary depending on whether instruction is delivered in rural or urban colleges. Generally, these challenges falls into three (03) broad categories i.e. (i) those related to students, (ii) those related to teachers, and (iii) those associated with institutional facilities. The present paper was conducted with the objective to identify these challenges in both rural and urban settings and propose possible potential solutions. In this paper a qualitative research approach was employed for capturing in-depth insights from the field. Data was gathered through semi-structured interviews and questionnaires administered to four (04) English language teachers from selected areas. The study findings concludes that student-related issues include (i) limited vocabulary mastery, (ii) low levels of motivation, (iii) insufficient parental support, and (iv) a lack of active participation in classroom activities. While on the hand teacher-related challenges (i) limited familiarity with information technology, (ii) inadequate mastery of diverse teaching methods, and (iii) a shortage of professional training opportunities are included. Furthermore, facility-related challenges were also significant, particularly in rural colleges, where problems such as the absence of suitable buildings, a shortage of computers, and the lack of multimedia resources like LCD projectors were observed.